Evaluation of focal liver lesions by magnetic resonance imaging and correlation with pathology - Rao M., Uma Maheswara; Ch., Lakshman Rao (International Journal of Research in Medical Sciences, 2016)
Background: The goals of imaging in focal liver lesions is to assess the number, size, location and characterize the lesions as benign / malignant with newer imaging modalities and confirmation of pathology by Fine needle aspiration cytology or by biopsy. This is essential for treatment planning and prognosis. Methods: A total of 42 patients detected to have focal lesions in liver on ultra-sonogram were characterized on MRI on the basis of morphology, signal characteristics, enhancement patterns. Extra hepatic spread is suggested by capsular breach, peritoneal metastases and lymph node enlargement. Tissue diagnosis was obtained by fine needle aspiration cytology/ Tru cut biopsy/ surgery. Hemangiomas and simple cysts were followed up for an average period of 7.5 months by imaging without biopsy. Results: Out of 42 patients, 28 were males (68%) and 14 were females (32%). The age range was 20 to 70 years with a mean age of 51 years for malignant lesions. The right lobe of liver was involved in 26 (62%), left lobe in 7 (17%) and both lobes in 9(21%) cases. There were 24 benign and 18 malignant lesions. The mean ADC value was 2.092 X 10-3 sec/ mm2 and 1.241 X 10-3 sec/ mm2 for benign and malignant lesions respectively. The difference in mean ADC values in both the groups was significant (p<0.0001). Conclusions: MRI was able to predict diagnosis in 38 of the 42 lesions (90%) which were proved on pathology or by follow up imaging. MRI could not provide specific diagnosis in two early abscess, one each of multifocal hepatocellular carcinoma and regenerative nodules. Thus MR imaging is a powerful tool for the evaluation of focal liver lesions.